Paradoxical Exacerbation of Symptoms with Obstruction of the Venous Outflow after Gamma Knife Radiosurgery for Treatment of a Dural Arteriovenous Fistula of the Cavernous Sinus - Ko, Jun Kyeung (J Korean Neurosurg Soc, 2015)
A 59-year-old female presented with progressive right proptosis, chemosis and ocular pain. An imaging work-up including conventional catheter angiography showed a right-sided dural arteriovenous fistula of the cavernous sinus, which drained into the right superior petrosal sinus, right superior ophthalmic vein, and right inferior ophthalmic vein, and cortical venous reflux was seen via the right petrosal vein in the right posterior fossa. After failure of transvenous embolization, the patient underwent Gamma Knife radiosurgery (GKRS). At one month after GKRS, she developed increasing ocular pain and occipital headache. Repeat angiography showed partial obliteration of the fistula and loss of drainage via the superior and inferior ophthalmic veins with severe congestion, resulting in slow flow around the right cerebellar hemisphere. Prompt transarterial embolization relieved the patient's ocular symptoms and headache. We report on a case of paradoxical exacerbation of symptoms resulting from obstruction of the venous outflow after GKRS for treatment of a dural arteriovenous fistula of the cavernous sinus.